2017
DOI: 10.1002/chem.201605617
|View full text |Cite
|
Sign up to set email alerts
|

Seedless Synthesis of Monodispersed Gold Nanorods with Remarkably High Yield: Synergistic Effect of Template Modification and Growth Kinetics Regulation

Abstract: Gold nanorods (AuNRs) are versatile materials due to their broadly tunable optical properties associated with their anisotropic feature. Conventional seed-mediated synthesis is, however, not only limited by the operational complexity and over-sensitivity towards subtle changes of experimental conditions but also suffers from low yield (≈15 %). A facile seedless method is reported to overcome these challenges. Monodispersed AuNRs with high yield (≈100 %) and highly adjustable longitudinal surface plasmon resona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…29,30 Later, El-Sayed and co-workers 31 showed that decreasing the solution pH with HCl could produce nanorods smaller than those obtained with conventional seeded syntheses. Conversely, another study 32 catechol (1,2-dihydroxybenzene), resorcinol (1,3-dihydroxybenzene), 33 dopamine (3,4-dihydroxyphenethylamine), 34 1,2,4-trihydroxybenzene, 35 pyrogallol, 36 and 5-bromosalicylic acid 37 have been used to further improve the monodispersity and control the nanorod dimensions in the seed-mediated and seedless syntheses. Recently, dopamine was used both as a reducing agent and as a stabilizer whereby the CTAB concentration could be reduced to 22 mM from 100 mM with tunable LSPR wavelengths between 700 and 1050 nm in high yield.…”
Section: ■ Introductionmentioning
confidence: 99%
“…29,30 Later, El-Sayed and co-workers 31 showed that decreasing the solution pH with HCl could produce nanorods smaller than those obtained with conventional seeded syntheses. Conversely, another study 32 catechol (1,2-dihydroxybenzene), resorcinol (1,3-dihydroxybenzene), 33 dopamine (3,4-dihydroxyphenethylamine), 34 1,2,4-trihydroxybenzene, 35 pyrogallol, 36 and 5-bromosalicylic acid 37 have been used to further improve the monodispersity and control the nanorod dimensions in the seed-mediated and seedless syntheses. Recently, dopamine was used both as a reducing agent and as a stabilizer whereby the CTAB concentration could be reduced to 22 mM from 100 mM with tunable LSPR wavelengths between 700 and 1050 nm in high yield.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Improve morphology Adjusting the concentrations of CTAB and sodium oleate Roach et al (2018) Promote the anisotropic growth Introducing a weaker reducing agent (hydroquinone), with template modification Liu et al (2017a) Introducing a weaker reducing agent (resveratrol) Wang et al (2016b) Improve the yield Increasing the concentration of the gold precursor solution Yan et al (2018) Yang et al (2016b) Human induced pluripotent stem cells loaded with GNRs @SiO2@CXCR4 nanoparticles which were pre-treated with mitomycinC (MMC)…”
Section: Seedless Methodsmentioning
confidence: 99%
“…The use of HQ has been exploited for the seedless modified protocol proposed by Wang in 2017 [ 38 ]. The authors introduced two main modifications: the introduction of 5-bromosalicylic acid (5-BA) as template regulator at the beginning of the micellar formation and the addition of HQ as weak reducing agent during the growth phase ( Figure 5 ).…”
Section: Synthesismentioning
confidence: 99%
“… Scheme of seedless synthesis technique based on the use of 5-bromosalicylic acid and hydroquinone. Reproduced from [ 38 ] with permission from the John Wiley and Sons. …”
Section: Figurementioning
confidence: 99%